Spontaneous Intracranial Hypotension Presenting With Frontotemporal Dementia: A Case Report - Ozyigit, Ahmet; Michaelides, Costas; Natsiopoulos, Konstantinos (Frontiers in Neurology, 2018)
Spontaneous intracranial hypotension (SIH) is a rare and often underdiagnosed condition, which commonly results from a cerebrospinal fluid leak. The classic clinical presentation of SIH is a postural headache and dizziness. Less frequent complications include nausea, neck stiffness, and even coma. This case report describes a 70-year-old woman with an initial complaint of postural headaches and sleep attacks, who developed a 22-month progressive history of personality and behavioral changes, cognitive decline, urinary incontinence, chorea, and dysarthria. Although no specific cerebrospinal fluid leak was identified, the patient was suspected of having SIH and her symptoms completely reversed after a 2-month course of steroids. This case highlights that SIH represents a rare and reversible cause of a wide spectrum of neurological symptoms, including dementia. Neurologists should be aware of this diagnosis when evaluating patients with neurological signs and symptoms that cannot otherwise be explained.